HIVEP1 Is a Negative Regulator of NF-κB That Inhibits Systemic Inflammation in Sepsis - Matsumoto, Hisatake; Scicluna, Brendon P.; Jim, Kin Ki; Falahi, Fahimeh; Qin, Wanhai; Gürkan, Berke; Malmström, Erik; Meijer, Mariska T.; Butler, Joe M.; Khan, Hina N.; Takagi, Tsuyoshi; Ishii, Shunsuke; et al. (Frontiers in Immunology, 2021)
Our previous work identified human immunodeficiency virus type I enhancer binding protein 1 (HIVEP1) as a putative driver of LPS-induced NF-κB signaling in humans in vivo. While HIVEP1 is known to interact with NF-ĸB binding DNA motifs, its function in mammalian cells is unknown. We report increased HIVEP1 mRNA expression in monocytes from patients with sepsis and monocytes stimulated by Toll-like receptor agonists and bacteria. In complementary overexpression and gene deletion experiments HIVEP1 was shown to inhibit NF-ĸB activity and induction of NF-ĸB responsive genes. RNA sequencing demonstrated profound transcriptomic changes in HIVEP1 deficient monocytic cells and transcription factor binding site analysis showed enrichment for κB site regions. HIVEP1 bound to the promoter regions of NF-ĸB responsive genes. Inhibition of cytokine production by HIVEP1 was confirmed in LPS-stimulated murine Hivep1-/- macrophages and HIVEP1 knockdown zebrafish exposed to the common sepsis pathogen Streptococcus pneumoniae. These results identify HIVEP1 as a negative regulator of NF-κB in monocytes/macrophages that inhibits proinflammatory reactions in response to bacterial agonists in vitro and in vivo.